The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s00253-014-6103-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mechanisms of Cu(II) sorption from aqueous solution by using bioflocculant MBFR10543

Abstract: This paper investigated the characteristics of Cu(II) sorption from aqueous solution by using bioflocculant MBFR10543 and discussed the mechanism during the sorption process. Results have demonstrated that the removal efficiency of Cu(II) reached 96.9% by adding MBFR10543 in two stages, separately, 1.5 × 10(-2) % (w/w) in the 1.0-min rapid mixing (180 rpm) and 2.0 × 10(-2) % (w/w) after 2.0-min slow mixing (80 rpm), with pH value fixed at 6.0. Cu(II) sorption process could be described by the pseudo-second-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…It is noteworthy that the pH range of 5.5–8.5 just covered the raw pH value of the swine wastewater (6.7), so that pH adjustment was not needed in this experiment from a practical standpoint. Similar researches reported that Paenibacillus polymyxa performed well under natural pH condition 14 , while a weak acidic was favored for Streptomyces 20 .…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…It is noteworthy that the pH range of 5.5–8.5 just covered the raw pH value of the swine wastewater (6.7), so that pH adjustment was not needed in this experiment from a practical standpoint. Similar researches reported that Paenibacillus polymyxa performed well under natural pH condition 14 , while a weak acidic was favored for Streptomyces 20 .…”
Section: Resultssupporting
confidence: 69%
“…The same phenomenon was observed in the cultivation of Ochrobactrum ciceri W2 18 . After the strain entered into its death phase at 72 h, cell number began to decline, and consequently the EPS yield decreased as well until to 1.26 g/L, which may be due to cell autolysis and the decreasing in enzymatic activity 14 . Additionally, the highest EPS value of 3.01 g was higher than that reported by Aljuboori et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the increasing requirement to environmental quality, production, characterization of bioflocculants, and their performances have been investigated in the treatment of dying wastewater (Liu et al 2009), swine wastewater (Guo et al 2013), and heavy metal ions (Guo 2015). As a result, active ingredients of the bioflocculants and their mechanisms during flocculation process were not entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the serious health and environmental concerns caused by the traditional flocculants, and the increasing demand for environmental friendly flocculants, bioflocculant, secreted during microorganisms’ metabolic process, has been attracted scientific attention due to its biodegradability and negligible secondary pollution, and has been regarded efficiently in removing suspended solids, organics, dye pigments, heavy metal ions and so on, from wastewaters on laboratory scales (Guo, ). Currently, high costs associated with relatively expensive substrates (such as beef extract, peptone and so on) gradually became impediments for the production and application of the bioflocculant (Zhao et al ., ), and thus, attempts have been made to get new efficient mutant and seeking for low‐cost substrates to reduce the production cost (More et al ., ; Guo & Ma, ; Guo et al ., ).…”
Section: Introductionmentioning
confidence: 99%